Avaliação nutricional do farelo de trigo para gatos - Ludmila Barbi Trindade (2015)
The present aimed to evalute the wheat bran for adult cats from extruded diets containing increasing levels of wheat bran, 15, 30 and 45%, replacing a control diet.Using the digestibility and metabolizable energy obtained values for each diet, were calculated the digestibility and metabolizable wheat bran values, for the specie, through substitution and regression methods. Adult cats were fed with free FT diet (control diet) and test diets including 15, 30 and 45% FT in substitution for macro ingredients of the controldiet.The chosen experimental design was a double Latin square, four by four, with two animals per treatment period, totaling eight replicates per treatment.The use of FT reduced the digestibility ofMS, MO, PB, EE, FDN, FDA, EM ofdiets (p <0.05), however, it did not show a pronounced impair on the digestibility of PB, EE (p> 0.05) when included 15% PB, and up to 30% EE.The high percentage of total dietary fiber FT has low solubility and fermentability, which can justify digestibility and EM reduction on diets. With the average values of digestibility coefficients and EM on evaluated diets, were determined the digestibility of each wheat bran nutrient for test diets, determined by substitution and regression methods.Finally, a correlation study was conducted, trough the analysis of multiple linear regression between the chemical composition of the experimental diets and the coefficients of apparent digestibility of the nutrients,in order to determine the PD, ED and EMA from diets forcats containing FT. The prediction equations with only one dependent variable analyzed, were significant (p <0.0001) and showed high R², suggesting that is possible to estimate the PD, ED and EMA from diets containing wheat bran for cat by determining only one chemical component of the diet.We concluded that the FT is a low energy ingredient, with restricted use on cats diets and the inclusion of 15% of this ingredient shows less interference on digestibility of food for adult cats.